Signal representation and analysis using time-frequency transforms - Zhang, Feng (2008)
This thesis studies the analysis of time-varying signals using time-frequency transforms. The research on time-frequency analysis is to understand and develop the transforms that can faithfully describe a signal in the time frequency plane.